Analisis Kemandirian Belajar Siswa Madrasah Tsanawiyah Negeri di Kota Pontianak pada Mata Pelajaran IPA - Elistiani Elistiani; Eny Enawaty*; Ira Lestari; Rahmat Rasmawan; Rody Putra Sartika (Universitas Syiah Kuala, 2022)
The Covid-19 pandemic has led to the emergence of a prototype curriculum that focuses on inculcating the character of Pancasila students, one of which is independent. This study aims to describe the learning independence of students at MTs Negeri 2 Pontianak in the even semester of the 2020/2021 academic year (online) and the odd semester of the 2021/2022 academic year (offline). The method in this study is a descriptive method with a quantitative approach. The subjects in this study were students of one class at MTs Negeri 2 Pontianak, totaling 27 students. Data collection techniques in this study used indirect communication techniques of a student learning independence questionnaire consisting of 30 statements with six aspects, documentation study techniques in the form of even and odd semester science test scores, and direct communication in the form of unstructured interviews with students to support research data. The data analysis technique used is descriptive statistics. The results showed that in the even semester of the 2020/2021 academic year (online) and the odd semester of the 2021/2022 academic year (offline) students of MTs Negeri 2 Pontianak had independent learning in the independent category. There is no significant difference between online and offline learning independence. And There is no significant correlation between student learning independence and the science test results of MTs Negeri 2 Pontianak students in the even semester of the 2020/2021 (online) and the odd semester of the 2021/2022 (offline), but students have independence.